Analisis Komparatif Kebijakan Pendidikan di Indonesia dan Finlandia - Salman Al Farisy; Nathasya Fitria; Garin Wulan Raja; Nurul Kamaly; Afrijal; Ibnu Phonna Nurdin (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study aims to analyze the comparative education policies of Indonesia and Finland, focusing on curriculum, teacher autonomy, educational equity, and evaluation systems, and their implications for national education reform. This research uses a qualitative approach with a comparative study method through a review of academic literature. The results indicate that fundamental differences between the two countries lie not only in policy design but also in the paradigm of educational governance. Indonesia tends to adopt a control-based governance approach characterized by reactive curriculum changes, a predominance of standards-based evaluations, and a high administrative burden on teachers. In contrast, Finland implements trust-based governance, emphasizing policy stability, teacher professional autonomy, equity-based equity, and formative evaluation oriented toward student development. These findings reveal a mismatch between Indonesia's educational goals, which focus on developing competencies and character, and policy instruments that are still based on control and standardization. As a contribution, this study offers a hybrid governance model framework that integrates policy accountability with strengthening trust in teacher professionalism. Policy implications include long-term curriculum simplification, reducing teacher administrative burdens, strengthening area-based interventions for educational equity, and transforming the evaluation system toward diagnostic and formative assessments.